TEACHING INNOVATION BY USING TASK BASED LEARNING - Surya, Satyawati (Fakultas Ilmu Budaya, Universitas Mulawarman, 2017)
This study is concerned on the notion of using Task-Based Learning for teaching English Integrated Skills to the students of the first semester of English Department, Mulawarman University. In fact, most students have minimum knowledge and ability on English skills when they attend the class for their first semester. They also have lacks knowledge on grammar and limited vocabulary. The other factors determine the students’ success in learning a language are teaching methods, teachers’ competence on language and pedagogy, school environment, facilities and media. The limited and lacks of those factors cause unsuccessful in learning a language. A teaching innovation is necessary to be applied to the students in order that the students are able to know well about the language knowledge and theory, all at once, they can practice it although it is just in the classroom situation. The writer intends to introduce and try out the method of Task-Based Learning to the students while they are learning English. Task based learning is a different way to teach languages. It can help the student by placing her in a situation like in the real world. A situation where oral communication used is essential for doing a specific task. Task-based learning offers the student an opportunity to do exactly meaningful tasks or activities. The primary focus of classroom activity is the task and language is the instrument which the students use to complete it. The writer is interested to describe on how the Task-Based Learning is and what activities can be applied to teach English by using this method. This study produces some kinds of activities to teach English based on the topics which the activities on each topic is divided into three phases. Actually, it is the product of doing design and development research. It produces the teaching instructional model which applies Task-Based learning that can be utilized for teaching integrated skills. Keywords: task-based learning, phases of learning, integrated skills